Potensi Gangguan Gulma pada Tiga Sistem Budidaya Padi Sawah - Zarwazi, Lalu Muhamad; Chozin, Muhammad Achmad; Guntoro, dan Dwi (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2016)
ABSTRACTWeeds has become a big problem in system of rice intensification (SRI), integrated crop management (ICM) and conventional cultivation systems. The objective of the research was to study the dominancy and potential of harmful effect of weed in these three cultivation systems. The research was conducted at Sukamandi research station of Indonesian Center for Rice Research, Subang, from November 2013 to April 2014 during rainy season. The experiment was arranged in a split plot design with four replications. The cultivation systems was main plot consisted of system of rice intensification (SRI), integrated crop management (ICM) and conventional system. The weeding techniques as subplot consisted of no weeding, manual weeding, mechanical weeding and chemical weeding. The result showed that based on dry mass of weeds the highest risk of weed was exhibited at SRI with total dry mass of weed 51.53 g m-2 (0.5 ton ha-1) and the lowest was at conventional system with 32.45 g m-2 (0.3 ton ha-1). Proper weed control increased rice production by 28.9% for SRI, by 29.4% for ICM and by 14.6% for conventional cultivation systems. Keywords: dominant, weeding technique, SRI, ICM, conventional system